Pemanfaatan Limbah Daun untuk Ecoprint dalam Upaya Pemberdayaan Ibu-Ibu Desa Teguhan - Tiara Intan Cahyaningtyas; Nur Samsiyah; Endang Sri Maruti; Sri Budyartati; Rafika Andan Sari; Rossy Qoimatul Fadlila (Madani : Indonesian Journal of Civil Society, 2022)
The purpose of this service program is to empower PKK women in the village of Teguhan in utilizing leaf waste for ecoprints which have a high selling value and can develop into businesses. Participants in this service were 15 people consisting of PKK women from Teguhan village. The service activity was carried out at the Teguhan village office for 3 days, namely on 18-19 February 2022. The service was carried out by taking care of permits, recording the number of PKK women, socializing eco print materials and mentoring and evaluating activities. Based on the results and discussion, it can be concluded that this activity is very beneficial for the participants, namely the PKK women in Teguhan Village. The results of this community service resulted in an understanding of the material about eco print with a fairly good achievement with an average of 63%. The results of the demonstration activities and participants' skills in making eco prints showed very good results, with average achievements of 85% and 84%, respectively. The participants received and absorbed the training materials on making eco prints well. Furthermore, the participants were able to demonstrate directly how to make eco prints using certain techniques so that the results obtained were durable and of high quality.